Pengetahuan Ibu Menopause Tentang Perubahan Fisiologi dan Psikologi Pada Masa Menopause - Ni Made Rai Widiastuti; Yeanneke Anita Kopa (Jurnal Genta Kebidanan, 2020)
The purpose of the study was to determine the knowledge of menopausal mothers about changes in physiology and psychology during menopause based on education and work. The research method used descriptive research with a cross-sectional approach. The number of samples in this study was 64 people. The method of collecting data using a questionnaire and the sampling technique used is a consecutive sampling. Processing data using data tabulation. This study found that the knowledge of menopausal mothers about changes in physiology and psychology during menopause was almost entirely, namely, 32 people (76.2%) had good knowledge, a small number were 9 people (21.4%) had sufficient knowledge and a small number were one (2.4%) have less knowledge. Based on the educational characteristics of all respondents included in the higher education group, they have good knowledge. Based on the job characteristics of all respondents included in the working group, they have a good level of knowledge.